Mcdonalisasi ala Ritzer dan Modernitas Juggernaut ala Gidden - Munadhil Abdul Muqsith; Radita Gora Tayibnapis (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
McDonalization in the world created a new concept of a new modernization style of Popular Culture. The representation built by McDonald's then changed the capitalization system of the fast-food industry to one that prioritizes time and cost efficiency and offers the prestige of higher consumer class values through a sign system and the formation of a structure in a new service culture at McDonald's. Through a literature review viewed from the perspective of Ritzer's social definition paradigm and Giddens's Modernity, it can be explained that McDonald's makes a mass culture system at the global level for fast food restaurants and a modern system of product services. Meanwhile, McDonald's seems to be simulating a sign and icon that attracts consumers' attention to focus on the goal of forming a higher consumption society with the aim of supporting a smooth capitalization system in the culture industry.Keywords: Modernity; Ritzer; Gidden; Modern Culture Abstract McDonalisasi di dunia menciptakan sebuah konsep baru tentang Budaya Populer baru ala modernisasi. Representasi yang dibangun McDonald kemudian merubah sistem kapitalisasi industri makanan cepat saji menajdi yang mengutamakan efisiensi waktu dan biaya serta menawarkan prestise nilai kelas konsumen yang lebih tinggi melalui sistem tanda dan pembentukan struktur pada budaya pelayanan baru di McDonald. Melalui kajian literatur dilihat dari perspektif paradigma definisi sosial Ritzer dan Modernitas Giddens, dapat dijelaskan bahwa McDonald menjadikan sistem budaya massa ditingkat global untuk resto cepat saji dan sistem modern dari layanan produknya. Adapun McDonald terlihat mensimulasikan sebuah tanda dan icon yang menarik perhatian konsumen untuk menitik beratkan pada tujuan membentuk masyarakat konsumsi yang lebih tinggi dengan tujuan mendukung lancarnya sistem kapitalisasi di industri budaya.Keywords: Modernitas; Ritzer, Gidden; Budaya Modern